Linguistics an introduction - McGregor, William 1952- (London Bloomsbury Academic, 2015)
"This is the new edition of Linguistics: An Introduction. It is a bestselling introductory textbook for all students of linguistics and language studies. This reworked edition features: [bullet] new chapters on sign languages, writing, and text and discourse. [bullet] coverage of writing in electronic media[bullet] revised and updated chapters on languages of the world and psycholinguisticsFirmly based around taught courses and catering to student needs, it addresses all the topics that a student will need in their initial and subsequent study of language. With key terms, further reading, questions at the end of each chapter, exercises and key paragraphs in stand-out boxes, this is a firmly pedagogic text that takes difficult concepts and explains them in an easy to understand way, with examples taken from a range of languages across the world. Global in its scope and comprehensive in its coverage, this is the textbook of choice for linguistics students. The book comes with a large Companion Website, also extensively revised and expanded, and, for lecturers and instructors, a comprehensive Answer Book is also available to go along with the questions throughout the chapters"--Provided by publisher.
"Linguistics is a fresh and contemporary introductory textbook for all students of linguistics and language studies. Firmly based around taught courses and catering to student needs, it addresses all the topics that a student will need in their initial and subsequent study of language. With key terms, further reading, questions at the end of each chapter, exercises and key paragraphs in stand-out boxes, this is a firmly pedagogic text that takes difficult concepts and explains them in an easy to understand way, with examples taken from a range of languages across the world. Global in its scope and comprehensive in its coverage, this is the textbook of choice for linguistics students"--Provided by publisher.
Machine generated contents note: -- List of Figures List of MapsList of TablesPrefaceAcknowledgements Abbreviations and Conventions Used in Examples 1. IntroductionPart I LANGUAGE: SYSTEM AND STRUCTURE2. Sounds of Language: Phonetics and Phonology3. Structure of Words: Morphology4. Lexicon5. Structure of Sentences: Syntax6. MeaningPart II LANGUAGE: A HUMAN PHENOMENON7. Sociolinguistics: Language in Its Social Context8. Text and Discourse9. Psycholinguistics: Language, the Mind and the Brain10. Language Acquisition11. Language in Its Biological ContextPart III LANGUAGE: UNIFORMITY AND DIVERSITY12. Sign languages13. Writing14. Unity and Diversity in Language Structure15. Language Change16. Languages of the WorldGlossaryReferencesLanguage IndexName IndexSubject Index.
Includes bibliographical references (pages 433-453) and index.
Keywords: Linguistics